Silver lining: a ray of hope through strength-based approach in the health care setting - Kanmani, Thiruchengodu Raju; Mathai, Jeslet T.; Gurrapu, Rakesh (International Journal Of Community Medicine And Public Health, 2022)
The strength-based approach challenges the traditional deficit model applied in psychosocial care practice, which takes an all-encompassing perspective. Creating a comprehensive portrait of each person's life and working in a multidisciplinary team collectively analyses the full capabilities and circumstances of individuals or families. This paper employs case illustrations to demonstrate how psychosocial care providers can do assessments and interventions based on a strength-based approach to improve the quality of life of patients and their families. The study adopted cases from the case file and derived how strength-based approaches can be utilized for the patients referred for psychosocial assessment and designing psychosocial care plan in the tertiary care hospital. The case illustrations depict practice through strength-based approach. The assessments were conducted, plans were made, and interventions focused on the strengths in various domains. The result portrayed strength of each case on innate, acquired/learned, supportive strengths in personal, family, social and health domains of life. The analysis of the strengths of the patient allowed to develop a tailor-made intervention plan, and these interventions have resulted in empowerment and recovery. The strength-based approach is one of the approaches which came differently from the deficit models of psychosocial practice. In India, the practice of a strength-based approach for interventions in various fields is in its infancy. The legislations in India have provisions that support a strength-based approach.